The five-star weekend - Hilderbrand, Elin (Little, Brown, 2023)
Hollis Shaw's life seems picture-perfect. She's the star of the popular food blog, Hungry with Hollis, and is married to Matthew, a dreamy heart surgeon. But after she and Matthew get into a heated argument one snowy morning, Matthew leaves for the airport and is killed in a car accident. The cracks in Hollis's perfect life-her strained marriage and her complicated relationship with her daughter, Caroline-grow deeper. When Hollis hears about something called the "Five-Star Weekend"-a woman invites her best friend from her teenage years, her twenties, her thirties, and mid-life-Hollis decides to host her own "Five-Star Weekend" on Nantucket. But her weekend won't be the Hallmark movie one might expect. Hollis's childhood friend, Tatum, invites Hollis's first love, Jack Finigan, to spend time with them, stirring up old feelings. Meanwhile, Tatum is forced to play nice with Dru-ann, Hollis's best friend from UNC Chapel Hill. Dru-ann's career as a prominent Chicago sports agent is on the line after her comments about a client's mental health issues are misconstrued online. Brooke, Hollis' friend from their thirties, has just discovered that her husband is having an inappropriate relationship with a woman at work. Again! She runs into an old "friend," Electra, a troublemaker who had ousted Brooke from the Wellesley mom friend group where Brooke and Hollis met years before. And then there's Gigi, a stranger to everyone (including Hollis) who reached out to Hollis on her blog. Gigi carries an unusual grace and, as it happens, has many secrets. It will be a weekend like no other.